Ambivalent Effects of Stay-at-Home and Working Mother Stereotypes on Mothers' Intergroup and Interpersonal Dynamics. Issue 1 (2nd January 2020) - Odenweller, Kelly G.; Rittenour, Christine E.; Dillow, Megan R.; Metzger, Aaron; Myers, Scott A.; Weber, Keith
ABSTRACT: We applied foundational intergroup research to a quasi-experiment with stay-at-home mothers (SAHMs) and working mothers (WMs) in order to investigate mothers' contributions to the pressures of idealized motherhood. After viewing a description of a target mother, who portrayed one of seven empirically-derived mother stereotypes, participant mothers ( N = 529) reported on their intended attitudes, positive and negative emotions, and facilitative and harmful behaviors toward another mother. Results revealed the ambivalent effects of stereotypes on mothers' intergroup and interpersonal dynamics. Specifically, the content of the ideal and lazy stereotypes elicited mothers' contempt, whereas mothers' SAHM and WM group identities influenced both positive and negative responses to the stereotypes that embody intensive mothering (e.g., ideal, overworked, family and home oriented) . The discussion highlights the implications and contributions of these findings to intergroup and family communication scholarship.